Dimensioning of survivable WDM networks. - Van Caenegem, B. (IEEE Journal on selected areas in communications)
In this paper routing, planning of working capacity, rerouting, and planning of spare capacity in wavelength division multiplexing (WDM) networks are investigated. Integer linear programming (ILP) and simulated annealing (SA) are used as solution techniques. A complex cost model is presented. The spare capacity assignment is optimized with respect to three restoration strategies. The benefit of wavelength conversion, the choice of the fiber line system, and the influence of cost parameter values are discussed, with respect to the different restoration strategies and solution techniques. Wavelength conversion is found to be of limited importance, whereas tunability at the end points of the connections has substantial benefits